A dynamic, modifiable model for estimating cost‐effectiveness of smoking cessation interventions in pregnancy: application to an RCT of self‐help delivered by text message. (5th December 2018) - Jones, Matthew; Smith, Murray; Lewis, Sarah; Parrott, Steve; Coleman, Tim
Abstract: Background and Aims: Previous evaluations of smoking cessation interventions in pregnancy have several limitations. Our solution to these limitations is the Economics of Smoking in Pregnancy (ESIP) model, which estimates the life‐time cost‐effectiveness of smoking cessation interventions in pregnancy from a National Health Service (NHS) and personal social services perspective. We aim to (1) describe how ESIP has been constructed and (2) illustrate its use with trial data. Methods: ESIP links mothers' and offspring pregnancy outcomes to estimate the burdens of smoking‐related disease they experience with different rates of smoking in pregnancy, both in pregnancy and throughout their life‐times. Smoking rates are inputted by model users. ESIP then estimates the costs of treating disease burdens and also mothers' and offspring life‐years and quality‐adjusted life years (QALYs). By comparing costs incurred and healthy life following different smoking rates, ESIP estimates incremental cost‐effectiveness and benefit–cost ratios for mothers or offspring or both combined. We illustrate ESIP use using data from a pragmatic randomized controlled trial that tested a smoking cessation intervention in pregnancy. Results: Throughout women's and offspring life‐times, the intervention proved cheaper than usual care, having a negative incremental cost of £38.37 (interquartile range = £21.46–56.96) and it improved health, demonstrating a 0.04 increase in incremental QALYs for mothers and offspring, implying that it is 'dominant' over usual care. Benefit–cost ratios suggested that every £1 spent would generate a median of £14 (interquartile range = £8–20) in health‐care savings. Conclusions: Economics of Smoking in Pregnancy is the first economic model to link mothers' and infants' costs and benefits while reporting cost‐effectiveness in readily‐comparable units. Using ESIP with data from a trial which reported only short‐term economic analysis showed that the intervention was very likely to be cost‐effective in the longer term and to generate health‐care savings.